Một số giải pháp tăng cường công tác cán bộ nữ hiện nay ở TP. Đà Nẵng - Lê, Thị Tám (2011)
Tác giả: Lê Thị Tám, CN; Đỗ Thị Kim Lĩnh; Mai Thị Liên; Lê Thị Mỹ Hạnh; Hà Thị Hoa -- Từ khóa: Cán bộ nữ; Đà Nẵng